Smart Bulb Changer / Ruslan Abdul Jalil … [et al.] - Abdul Jalil, Ruslan; Othman, Hazreen; Mohd Zuber, Muhammad Syafiq; Mahat, Nurul Farahin; Mohamad Ali, Muhammad Nur Asraf; Ahmad, Asmadi; Musa, Mardiana; Ibrahim, Mohamad Shahril (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
"Smart bulb changer" is an innovation of installing and changing energy saving bulbs that was used as a down light at homes, offices, halls or the buildings. This innovation can avoid electric shock and body injury towards user as the bulb glass broken due to excess pressure or bulbs fall down during changing and installing. The idea of design concept is a combination of the application of "push up pencil" and "fishing reel system". The main focus in "Smart bulb changer" system is its ability to change and install of 6 or more bulbs at a time, safely, practically and easy to use. With this tool, indirectly help to reduce accident cases resulting from the changing and installation of the bulbs.